2020
DOI: 10.1016/j.jdiacomp.2020.107723
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory properties of antidiabetic drugs: A “promised land” in the COVID-19 era?

Abstract: Inflammation is implicated in the development and severity of the coronavirus disease 2019 (COVID-19), as well as in the pathophysiology of diabetes. Diabetes, especially when uncontrolled, is also recognized as an important risk factor for COVID-19 morbidity and mortality. Furthermore, certain inflammatory markers [ i.e. C-reactive protein (CRP), interleukin-6 (IL-6) and ferritin] were reported as strong predictors of worse outcomes in COVID-19 positive patients. The same biomarkers hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 158 publications
2
63
0
4
Order By: Relevance
“…However, five studies with a total of 6937 patients showed that metformin use was associated with reduction in mortality rate from COVID-19 infection [ 17 ]. The potential beneficial effect of metformin noted in COVID-19 infection might be attributed to its inherent anti-inflammatory properties beyond its glucose-lowering action and independent of glucose control, which could positively influence the prognosis and disease course of patients with DM and COVID-19 [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, five studies with a total of 6937 patients showed that metformin use was associated with reduction in mortality rate from COVID-19 infection [ 17 ]. The potential beneficial effect of metformin noted in COVID-19 infection might be attributed to its inherent anti-inflammatory properties beyond its glucose-lowering action and independent of glucose control, which could positively influence the prognosis and disease course of patients with DM and COVID-19 [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 5] An upregulation of DPP-4 in patients with DM remains a plausible explanation for the greater severity of COVID-19 in patients with DM [ 20 ]. A recent meta-analysis (n = 1607 patients with DM; 16 trials) found a significant reduction in inflammatory markers following DPP-4 inhibitors use compared with placebo [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antidiabetic drugs on the recovery of COVID-19 is beyond the scope of this study, which is reviewed elsewhere. [51][52][53][54]…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Besides glucose‐lowering effects, a growing body of literature indicates that GLP‐1RAs pose significant anti‐inflammatory properties and pulmonary protective effects. Anti‐inflammatory properties (with a focus on impact on CRP, IL‐6 and ferritin concentrations) of individual GLP‐1RAs have recently been extensively overviewed elsewhere by Katsiki and Ferrannini 30 …”
Section: Anti‐inflammatory Properties and Pulmonary Protective Effectmentioning
confidence: 99%